The Great Mysteries: Experiencing Catholic Faith from the Inside Out - Greeley, Andrew, (Rowman & Littlefield Publishers, 2003)
The Great Mysteries responds with passion and skill to the growing concerns of spiritual seekers and teachers of the Catholic faith. In radical, refreshing fashion, Greeley explores 12 essential questions of faith and grounds them in human experience. With the skill of a master storyteller and the passion of a deep believer, Greeley contemplates questions at the heart of human life—is there any purpose in my life? Are there any grounds for hope? Why is there evil in the world?—and reveals how the symbols, rituals, teachings and mysteries of Catholicism both shape and respond to these profound uncertainties.